CULTURAL DIPLOMACY AS AN IMPORTANT FACTOR IN THE FOREIGN POLICY OF THE STATE (ON THE EXAMPLE OF CHİNA) - Aziza Umarkulova; Etibor Sultanova (American Journals Publishing, 2023)
In the era of globalization and the information society, cultural diplomacy is an important tool for interaction in international relations. Being a form of «soft power», it helps to strengthen the country's positive image; strengthens international trust, develops interstate cooperation on the basis of transferring the national cultural code to the world community.Culture and politics closely interact in the process of sustainable development of China's cultural policy. The relevance of the topic under consideration is due to the fact that the state, thanks to the conduct of such a policy, sets the parameters for the implementation of cultural activities, determines the vectors for the development of culture, and also indicates promising areas for its support. Cultural policy forms the influence of various social actors on the ongoing changes in the life of society as a whole.The author proposes to study cultural diplomacy as an independent type of diplomacy at this stage of development of international relations, despite the close relationship of the phenomenon under study with such areas as: foreign cultural policy, public diplomacy, national branding, propaganda, soft power, and foreign policy image. The article presents various definitions of cultural diplomacy. An attempt was made to identify the main tools, mechanisms and resources of the studied type of diplomacy. The main principles of cultural diplomacy are given: intercultural dialogue; justice, equality; respect and recognition of cultural diversity and heritage; protection of international human rights; global peace and stability. The main aspects are described, through the disclosure of which one can study cultural diplomacy, namely: political, economic, security issues. The author focuses on the «soft power» of the modern foreign economic strategy of the People's Republic of China (PRC). The possibility of using the experience of cultural diplomacy of the PRC by other countries is emphasized.
Keywords: China, cultural diplomacy, cultural industry, soft power, public diplomacy